Identity Exploration in PhD Journey ‘Who Am I?’: An Auto-ethnographic Inquiry - Acharya, Kamal Prasad (Perspectives on Higher Education, 2024)
This auto-ethnographic inquiry offers a careful investigation of identity during the PhD research, shedding light on the complex interactions between personal experiences, scholarly activities, and social influences. It uses an auto-ethnographic qualitative research design that explores insights, reflections and experiences of the author from initial perturb to prolonged enthusiasm through introspective contemplation and active scholarly efforts, ultimately leading to a profound sense of fulfillment. Academic pursuits, such as writing research articles and presentations, become essential sources of inspiration for both professional and personal development and help to define the researcher's identity as both a practitioner and a scholar. Furthermore, a deeper awareness of overlapping identities and their larger implications for research, practice, and policy is gained through the researcher's connections with schools and community involvement projects. It has a significant academic accomplishment that is the result of intense study and persistent commitment. Working together with mentors and peers enhances the process by providing a variety of viewpoints and encouraging creativity. Even in the face of academic difficulties, celebrations and moments of unity serve as vital sources of inspiration. Additionally, PhD research addresses important issues and advance knowledge, offering insightful perspectives to academics and society alike. The PhD path ultimately demonstrates the transformative power of tenacity, teamwork, and intellectual contribution, leaving a lasting legacy on both individual and academic development and social implication.